Green areas and existing urban trees in sucre canton, Manabí, Ecuador - Cabrera Verdesoto, César Alberto (2024)
Green areas and trees an essential part of the ecological, social environmental and economic dimensions of urban sustainability. The objective of the research was to evaluate the coverage in the urban area the Sucre canton, with a green area 36 628,27 m2, where a census of existing parks was conducted, an inventory of forest species in the Bahía de Caráquez and Leonidas Plaza parishes was compiled. For this purpose, parks were considered clearly delimited public spaces, dominated by arboreal vegetation destined as public green areas; the research gathered dasometric information on trees from 18 locations including parks and road safety elements (avenues) in the canton; it also determined the areas, along with the total green area surface and the total urban population; according to the urban green index (IVU) it was 1,85 m2/hab. In order to get to know the trees in each park in depth, cartographic analysis was used in the preparation of maps and the georeferencing of green spaces. The ecological importance value index where the Azadirachta Indica species was the most representative species with 28,49% and the Tecoma stans with 1,03% the least representative, Margalef (2,85) reflected with medium diversity of species, Simpson (0,82) represented medium diversity and Shannon-Wiener (2,98) represented medium diversity. Concluding, that urban trees consist mainly of introduced species, with a low green index and a medium diversity according to the Margalef, Simpson and Shannon-Wiener indices.